PELATIHAN DASAR MERAJUT UNTUK ANAK ASUH YAYASAN RUMAH PAGI BAHAGIA DI BINTARO - Fivanda Fivanda; Canisha Chrystella; Michella Angelina (PROSIDING SERINA, 2021)
Since 2020 the Covid-19 pandemic has hit all provinces in Indonesia. The impact of the pandemic is not only on the business sector but on the development of the millennial generation of knowledge and expertise outside of basic education that has been obtained. The millennial generation must have to face the changes today, requiring future generations to be creative, innovative and have skills outside their scientific field. The basic knitting training activity was chosen as the first step in introducing and developing skills for the millennial generation. Profile of PKM partners, namely Rumah Pagi Bahagia Foundation, is a Foundation for Social Education Institutions for Orphans and the Environment. Mitra has more than 30 foster children of the millennial generation with an age range of 8-14 years whose mission is to create education and independence. The PKM team collaborated through basic training in knitting techniques to produce wearable products that were quite interesting. The partner's problem have limited ability of the partnership teaching team and wants to increase the insight of foster children. This basic knitting training aims to introduce and practice knitting skills made from yarn and hakpen. The knitting experience will be shared through video tutorials that have been prepared by the PKM team so that it can be used by foster children and their teaching staff to increase their knitting skills. It is also expected to be able to produce and develop disposable products that not only have innovative, creative value but also sell value to the public.